Transcriptomic Analysis of Avocado Hass (Persea americana Mill) in the Interaction System Fruit-Chitosan-Colletotrichum - Xoca-Orozco, Luis-Ángel; Cuellar-Torres, Esther Angélica; González-Morales, Sandra; Gutiérrez-Martínez, Porfirio; López-García, Ulises; Herrera-Estrella, Luis; Vega-Arreguín, Julio; Chacón-López, Alejandra (Frontiers in Plant Science, 2017)
Avocado (Persea americana) is one of the most important crops in Mexico as it is the main producer, consumer and exporter of avocado fruit in the world. However, successful avocado commercialization is often reduced by large postharvest losses due to Colletotrichum sp., the causal agent of anthracnose. Chitosan is known to have a direct antifungal effect and acts also as an elicitor capable of stimulating a defense response in plants. However, there is little information regarding the genes that are either activated or repressed in fruits treated with chitosan. The aim of this study was to identify by RNA-seq the genes differentially regulated by the action of low molecular weight chitosan in the avocado-chitosan-Colletotrichum interaction system. The samples for RNA-seq were obtained from fruits treated with chitosan, fruits inoculated with Colletotrichum and fruits both treated with chitosan and inoculated with the fungus. Non-treated and non-inoculated fruits were also analyzed. Expression profiles showed that in short times, the fruit-chitosan system presented a greater number of differentially expressed genes, compared to the fruit-pathogen system. Gene Ontology analysis of differentially expressed genes showed a large number of metabolic processes regulated by chitosan, including those preventing the spread of Colletotrichum. It was also found that there is a high correlation between the expression of genes in silico and qPCR of several genes involved in different metabolic pathways.